Descriptions of larvae of three Philopotamidae species from China (Insecta, Trichoptera) - Hu, Yan-Li; Tsring, Samten; Wang, Bei-Xin; Sun, Chang-Hai (Zootaxa, 2020)
Adults and larvae of the family Philopotamidae from Zhejiang Province, China, were examined and mtCOI gene sequences were extracted and analyzed, males and larvae of 3 species were successfully associated. The larvae of Chimarra sadayu Malicky 1993, Dolophilodes bellatula Sun & Malicky 2002, Wormaldia unispina Sun 1998 are described in detail and their diagnostic photographs and illustrations are presented. Diagnostic characters for genera and species are discussed.